2003
DOI: 10.1590/s0100-879x2003001100010
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of B lymphocyte function by an aqueous fraction of the ethanol extract of Cissampelos sympodialis Eichl (Menispermaceae)

Abstract: Cissampelos sympodialis Eichl species are used in folk medicine for the treatment of asthma, arthritis and rheumatism. In the present study, we investigated the immunomodulatory effect of an aqueous fraction of a 70% (v/v) ethanol extract of C. sympodialis leaves on B lymphocyte function. The hydroalcoholic extract inhibited the in vitro proliferative response of resting B cells induced by LPS (IC 50 = 17.2 µg/ml), anti-delta-dextran (IC 50 = 13.9 µg/ml) and anti-IgM (IC 50 = 24.3 µg/ ml) but did not affect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…On the other hand, warifteine may be modifying cyclic adenosine monophosphate (cAMP) levels by the inhibition of the phosphodiesterases in human neutrophils [34], which is resulting in the decrease of IgE production. This hypothesis seems also reasonable since the plant extract induced high levels of cAMP not only in anti-IgM stimulated B cell cultures [35] but also in guinea pig trachea strips [2]. The inhibition of the phosphodiesterase enzymes by warifteine may explain the up regulation of cAMP and the IgE inhibition.…”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, warifteine may be modifying cyclic adenosine monophosphate (cAMP) levels by the inhibition of the phosphodiesterases in human neutrophils [34], which is resulting in the decrease of IgE production. This hypothesis seems also reasonable since the plant extract induced high levels of cAMP not only in anti-IgM stimulated B cell cultures [35] but also in guinea pig trachea strips [2]. The inhibition of the phosphodiesterase enzymes by warifteine may explain the up regulation of cAMP and the IgE inhibition.…”
Section: Discussionmentioning
confidence: 87%
“…Its production in allergies is related with the Th2 cytokine profile. Rocha and col. () demonstrated that B cells in the presence of AFL and stimulated with several B cell stimuli did not present proliferate response and IgM production (Alexandre‐Moreira et al ., ). These effects were due to increasing levels of intracellular cAMP.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, it was observed that AFL increased the production of IL‐10 in Trypanosoma cruzi infected macrophages and inhibition nitric oxide production (Alexandre‐Moreira et al ., ). Moreover, AFL inhibited proliferative response of B cells with Toll‐like receptor stimuli and production of IgM and IgG by increasing the intracellular cAMP levels suggesting a therapeutic use of this extract in diseases associated with high production of immunoglobulin (Alexandre‐Moreira et al ., ; Rocha et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Do ponto de vista químico, vários alcalóides isoquinolínicos foram isolados de Cissampelos sympodialis, dentre os quais destacam-se: milonina (Freitas et al, 1995), warifteína (Cortes et al, 1995), metilwarifteína e laurifolina (Barbosa-Filho et al, 1997), liriodenina e roraimina (Lira et al, 2002). É uma espécie de grande importância na farmacologia pelas diversas atividades já confi rmadas, como espasmolítica e efeito citotóxico, atribuídos a warifteína e a milonina (Freitas et al, 1996;Melo et al, 2003), anti-anafi lática , antidepressiva (Almeida et al, 1998), antiinfl amatória (Lima et al, 2001;Falcão et al, 2005) que em parte esta relacionada à diminuição da função dos macrófagos (Alexandre-Moreira et al, 2003). Além disso, foi demonstrado que o tratamento oral com o extrato etanólico de suas folhas apresentaram um efeito imunomodulador (Bezerra-Santos et al, 2004) e que a warifteína é um componente ativo do extrato de C. sympodialis responsável por uma ação antialérgica (Bezerra-Santos et al, 2006).…”
Section: Introductionunclassified